Deference and defiance in Malaysia’s China policy:Determinants of a dualistic diplomacy - Cheng-Chwee Kuik; Yew Meng Lai (Cambridge University Press, 2023)
When do smaller states defer to and when do they defy stronger powers? How and why? This article traces and explains the changing patterns of deference and defiance in Malaysia’s China policy. There are three findings. First, deference and defiance are essential elements in all inter-state relations, especially asymmetric ones. The greater the power asymmetry, the greater the inclination to defer and defy. Second, states often pursue defiance and deference concurrently and selectively, with approaches adapted in accordance with changing external and internal conditions. The concurrent adoption of the two behaviors often manifest in hedging, an insurance-seeking policy aimed at offsetting multiple risks by counteracting the effects of the other behavior: deference without defiance risks subservience and dependency; defiance without deference invites hostility and confrontation. Third, the specific patterns and proportions of the deference–defiance mix are attributable more to domestic than external determinants, i.e., the needs to balance security, prosperity, and autonomy, as necessitated by the prevailing pathways of elite legitimation. This explains why Malaysia’s open deference vis-à-vis China has been accompanied by an indirect and quiet defiance especially in recent years, as best evidenced by the second Mahathir administration’s dualistic approaches toward the Belt and Road, South China Sea, and Xinjiang